Jean E. Conacher. Transformation and Education in the Literature of the GDR. Camden House, 2020. - Evelyn Preuss (Studies in 20th & 21st Century Literature, 2021)
Review of Jean E. Conacher. Transformation and Education in the Literature of the GDR. Camden House, 2020. xiv + 293 pp.
Keywords: East Germany; GDR; Intellectual History; Education; Socialism; GDR Literature; Eigensinn